# X(cosx)=3cosx

## Simple and best practice solution for X(cosx)=3cosx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for X(cosx)=3cosx equation:

Simplifying
X(cosx) = 3cosx
Multiply X * cosx
cosxX = 3cosx
Solving
cosxX = 3cosx
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3cosx' to each side of the equation.
-3cosx + cosxX = 3cosx + -3cosx
Combine like terms: 3cosx + -3cosx = 0
-3cosx + cosxX = 0
Factor out the Greatest Common Factor (GCF), 'cosx'.
cosx(-3 + X) = 0
Subproblem 1Set the factor 'cosx' equal to zero and attempt to solve:
Simplifying
cosx = 0
Solving
cosx = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
cosx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-3 + X)' equal to zero and attempt to solve:
Simplifying
-3 + X = 0
Solving
-3 + X = 0
Move all terms containing c to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + X = 0 + 3
Combine like terms: -3 + 3 = 0
0 + X = 0 + 3
X = 0 + 3
Combine like terms: 0 + 3 = 3
X = 3
Add '-1X' to each side of the equation.
X + -1X = 3 + -1X
Combine like terms: X + -1X = 0
0 = 3 + -1X
Simplifying
0 = 3 + -1X
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`

## Related pages

prime factorization for 26derivative of 2x 3converting percents to fractionssolving absolute value equations calculatoris2012x 6y 8100-55how do you graph y 2x 35x 2y 10132 prime factorization1 cos 6xsolve sin2x cos2xstep by step derivative solverderivative of sine cubedgraph x 6ycalculator for adding fractionshow to graph y 3xderivative tan 2xantiderivative of cos3xfind the prime factorization of 120find the prime factorization of 278y x9x63y 4x graphderive ln 2xwhat is the antiderivative of cos 2xprime factorization of 560derivitive of lnxy 5y 3y 0prime factorization of 19267-9-1256bsec2x 1simplify 2x 2xgcf of 84what is the prime factorization for 120multiply fractions calculator4x 5ysqrt 3 32x 5y 0graph 2-cosxgreatest common factor of 120kx2566ywhat is the gcf of 96 48 and 84what is the prime factorization of 196equation calculator with fractionshow to solve highest common factor2x 2 3 simplifyprime factorization 180sqrt 121what is the antiderivative of efractions calculator with steps850isprime factorization for 56sin2piax by c solve for ythe prime factorization of 92what is the prime factorization of 9123456789019w 117x 2 12x 4 0prime factorization 99roman numeral conversionsxln x5xmprime factorization 56999 roman numeralsfactor completely 2x2-2x-12simplify 625is 567 a prime numberwhat is cos 3xderivative ln 2xadding and dividing fractions calculator6x 5y 7